Processing-induced changes in components that affect the radical scavenging activity of ethanolic extracts from Neopyropia yezoensis - Hakuto Kageyama; Masaki Honda; Rikio Nakamura; Rungaroon Waditee-Sirisattha; Satoru Kamohara (AIMS Molecular Science, 2024)
Many marine red algae species are used as food sources around the world. Here, the study focuses on free radical scavenging properties as a beneficial activity of the red alga Neopyropia yezoensis (Susabi-nori), which is consumed in Japan, and investigates quantitative changes in the compounds that could affect the activity due to processing steps. It was found that the dried and roasted samples showed more active radical scavenging properties detected by the 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) assay compared to the fresh samples. The contents of phenolic compounds, mycosporine-like amino acids (MAAs), chlorophylls, and carotenoids were evaluated; it was suggested that an increase in phenolic compounds was responsible for the enhancement of the activity. On the other hand, no correlation with the activity was found for MAAs, chlorophylls, and carotenoids. Furthermore, by comparing three different sampling times (early December, early January, and early March), it was found that the sample taken in early December showed the highest radical scavenging activity. These results suggest that the useful activities of N. yezoensis, including its antioxidant activity, can be influenced by its processing steps and harvest time.